CARRYING OUT THEORETICAL STUDIES OF THE COTTON REGENATOR - Mamajanov, Shavkatjon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
In this paper, it was determined the strength of a newly installed slatted drum shaft by improving the design of the regenerator and conducting experiments on it. Based on the research, it was determined that the minimum value of the strength reserve coefficient is equal to 166, and it was concluded that this shaft fully meets the specified requirement for the device.